The effect of group cognitive behavioral therapy on stress, anxiety, and depression of women with multiple sclerosis - Saeid Pahlavanzadeh; Samira Abbasi; Nasrollah Alimohammadi (Wolters Kluwer Medknow Publications, 2017)
Background: One of the factors that could influence the quality of life in patients with multiple sclerosis, which is usually overlooked, is its psychological aspects. Considering the increasing acceptance of complementary medicine in the health system, this study was designed and conducted to determine the effect of group cognitive therapy on the stress, anxiety, and depression of women suffering from multiple sclerosis. Materials and Methods: This clinical trial was conducted among 70 women suffering from multiple sclerosis who were referred to the health centers of Isfahan. Participants were randomly allocated into two groups of intervention and control, each containing 35 patients. The intervention group received cognitive behavioral therapy as 8 90-minute group sessions (a session per week), and the control group participated in 4 group sessions to express their feelings and experiences. Data were gathered using the Depression Anxiety Stress Scale (DASS-24). Results: There was a significant difference between the mean score of stress (P = 0.03), anxiety (P = 0.02), and depression (P = 0.03) of the intervention and the control group immediately after and 1 month after the intervention. Least squares difference test showed that the mean score of stress (P = 0.02), anxiety (P = 0.02), and depression (P = 0.03) immediately and 1 month after the intervention was significantly lower in the intervention group. Conclusions: According to the results of the present study, cognitive behavioral therapy could decrease stress, anxiety, and depression in patients suffering from multiple sclerosis.